Differential Orthopedia Homeobox expression in pulmonary carcinoids is associated with changes in DNA methylation. Issue 12 (16th February 2022) - Moonen, Laura; Mangiante, Lise; Leunissen, Daphne J. G.; Lap, Lisa M. V.; Gabriel, Aurelie; Hillen, Lisa M.; Roemen, Guido M.; Koch, Alexander; van Engeland, Manon; Dingemans, Anne‐Marie C.; Foll, Matthieu; Alcala, Nicolas; et al.
Abstract: Limited number of tumor types have been examined for Orthopedia Homeobox (OTP) expression. In pulmonary carcinoids, loss of expression is a strong indicator of poor prognosis. Here, we investigated OTP expression in 37 different tumor types, and the association between OTP expression and DNA methylation levels in lung neuroendocrine neoplasms. We analyzed publicly available multi‐omics data (whole‐exome‐, whole‐genome‐, RNA sequencing and Epic 850K‐methylation array) of 58 typical carcinoids, 27 atypical carcinoids, 69 large cell neuroendocrine carcinoma and 51 small cell lung cancer patients and TCGA (The Cancer Genome Atlas) data of 33 tumor types. 850K‐methylation analysis was cross‐validated using targeted pyrosequencing on 35 carcinoids. We report bimodality of OTP expression in carcinoids (OTP high vs OTP low group, likelihood‐ratio test P  = 1.5 × 10 −2 ), with the OTP high group specific to pulmonary carcinoids while absent from all other cohorts analyzed. Significantly different DNA methylation levels were observed between OTP high and OTP low carcinoids in 12/34 OTP infinium probes (FDR < 0.05 and β ‐value effect size > .2). OTP low carcinoids harbor high DNA methylation levels as compared to OTP high carcinoids. OTP low carcinoids showed a significantly worse overall survival (log‐rank test P  = .0052). Gene set enrichment analysis for somatically mutated genes associated with hallmarks of cancer showed robust enrichment of three hallmarks in the OTP low group, that is, sustaining proliferative signaling, evading growth suppressor and genome instability and mutation. Together our data suggest that high OTP expression is a unique feature of pulmonary carcinoids with a favorable prognosis and that in poor prognostic patients, OTP expression is lost, most likely due to changes in DNA methylation levels. Abstract : What's new? Patients with pulmonary carcinoids that have low expression of the gene OTP (Orthopedia Homeobox) tend to have a worse prognosis. However, no mutations or genomic modifications have been found that explain the difference in OTP expression. Here, the authors analyzed DNA methylation data, and they found that changes in DNA methylation patterns were associated with the difference in OTP expression levels. These findings may suggest a role for epigenetic therapies in pulmonary carcinoid patients in the future.